Prevalence of Chronic Constipation and Chronic Diarrhea in Diabetic Individuals in the United States. (January 2019) - Sommers, Thomas; Mitsuhashi, Shuji; Singh, Prashant; Hirsch, William; Katon, Jesse; Ballou, Sarah; Rangan, Vikram; Cheng, Vivian; Friedlander, Daniel; Iturrino, Johanna; Lembo, Anthony; Nee, Judy
Abstract : INTRODUCTION: Diabetic individuals commonly report disordered bowel habits. This study aims to report the prevalence and associated factors of chronic diarrhea (CD) and chronic constipation (CC) in diabetics using a nationally representative sample of US adults. METHODS: Analyses were performed using data from subjects in the 2009-2010 National Health and Nutrition Examination Survey (NHANES) dataset who completed the Bowel Health Questionnaire. The NHANES dataset provides medical comorbidities, demographics, and dietary habits of a nationally representative group of adult survey participants in the United States. CC and CD were defined by Bristol Stool Form Scale (BSFS) Types 1 & 2 and BSFS Types 6 & 7 as the "usual or most common stool type, " respectively, and frequent laxative users were also defined as having CC. Co-variables for all subjects included demographic and lifestyle factors, and co-variables evaluated only in diabetics included treatment and severity markers for diabetes. RESULTS: We identified 661 diabetic subjects and 4488 non-diabetic subjects. Diabetic subjects (25.8%) reported disordered bowel habits. In unadjusted analysis, CD was more prevalent in diabetics than in non-diabetics (11.2% vs. 6.0%; p < 0.0001); however, the prevalence of CC was not significantly different between groups (14.6% vs. 11.2%; p = 0.126). When adjusting for covariates (e.g., BMI, gender, age, race/ethnicity, education level, etc.), diabetes itself remained associated with CD. Diabetic individuals with CD more frequently used drugs to lower blood sugar, and diabetic subjects with CC more frequently had poor kidney function. CONCLUSIONS: CD is significantly more prevalent in diabetics than in non-diabetics, whereas CC is not, and the association between CD and diabetes remains significant when adjusting for covariates. Use of medications that lower blood sugar is associated with CD in diabetic individuals, whereas poor kidney function is associated with CC in diabetics.